2018
DOI: 10.1371/journal.pone.0207634
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a faculty mentoring program in academic medicine

Abstract: The authors conducted a prospective longitudinal study from 2009 to 2016 to assess the short and long-term impact of a formal mentorship program on junior faculty satisfaction and productivity. Junior faculty mentees enrolled in the program and junior faculty without formal mentorship were administered surveys before and after the program to assess satisfaction with their mentoring experiences. Long-term retention, promotion, and funding data were also collected. Twenty-three junior faculty mentees and 91 juni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…didactic or peer-peer support) may not be suitable. Traditional hierarchical mentoring with unidirectional mentor-mentee relationships have worked well in large research institutes and shown transformative mentorship for junior faculty in the short [36] and long-term [37]. However, these relationships in regional settings can be time-consuming and challenging when mentors are faced with demands of working multiple roles (clinical, research, teaching) and having overlapping roles as mentors and supervisors [38].…”
Section: Discussionmentioning
confidence: 99%
“…didactic or peer-peer support) may not be suitable. Traditional hierarchical mentoring with unidirectional mentor-mentee relationships have worked well in large research institutes and shown transformative mentorship for junior faculty in the short [36] and long-term [37]. However, these relationships in regional settings can be time-consuming and challenging when mentors are faced with demands of working multiple roles (clinical, research, teaching) and having overlapping roles as mentors and supervisors [38].…”
Section: Discussionmentioning
confidence: 99%
“…4 Facilitated peer mentorship programs may be one mechanism to address the disparities that exist at the associate and full professor levels at the majority of academic medical centers and major universities. 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Peer mentorship may be of particular benefit to minority groups by facilitating a professional network that is requisite to obtaining a national reputation and academic promotion . Facilitated peer mentorship programs may be one mechanism to address the disparities that exist at the associate and full professor levels at most academic medical centers and major universities …”
Section: Discussionmentioning
confidence: 99%
“…(Table 1) Mentorship can be defined as a relationship between a mentor and mentee in which the mentor shares useful experience, knowledge, skills and offers advice, guidance, support, or opportunities to a mentee for overall development. [1][2][3][4][5][6]9,20,21 Aspects of mentoring overlap with coaching and being an advisor, but in its entirety, it encompasses much more. 20 A mentor focuses on long-term mentee professional growth without an absolute structure whereas a coach aims to improve short term performance or impart a skill using a structured program in a unidirectional, nonreciprocal interaction.…”
Section: Introductionmentioning
confidence: 99%
“…12 If early research success leads to future ideas that the mentee develops throughout their career, it may lead to the advancement of the field and increase academic productivity for both the specialty and institution. 1,5,6,11,19,21 By their senior years, residents will be focused on a near-future career trajectory. 11,26 Some questions that they will be pondering are whether to pursue a pediatric anesthesia fellowship or work as a generalist, what to look for in a fellowship program, and where to apply.…”
Section: Introductionmentioning
confidence: 99%